Reinforcing Factors Of Students Smoking Behavior In Pesantren Darul Hijrah Putra Martapura South Kalimantan - Musafaah Musafaah; Dina Yuniarti (Universitas Sari Mulia, 2018)
Objectives: Pesantren is one form of educational institutions in Indonesia that continues to grow in accordance with the needs of the era. One of the uniqueness of pesantren education is student or santri, learn and live in dormitory or cottage provided by pesantren. Students who study in pesantren are on average in the adolescent age range. Based on data from the care of students in Pondok Pesantren Darul Hijrah got records of smoking violations with the amount of data per year, from 1.684 the number of students in Pondok Pesantren Darul Hijrah son of the number of santri who smoke increased significantly from year to year. According to Lawrence W. Green there are three determinants of behavior for a person that is predisposing factor , enabling factorÂ and reinforcing factor ). The purpose of this study was to analyze the reinforcing factors of students smoking behavior at Darul Hijrah Putra Martapura Pesantren in South Kalimantan.Method: This research used cross sectional approach. The sample is students from Darul Hijrah Putra Pesantren in Martapura South Kalimantan as much as 70 people by Quota sampling. The independent variables in this study were male parents' smoking behavior and smoking status of teacher, smoking status of roommate and smoking status of non roommate. The dependent variable is smoking behavior on the students of Darul Hijrah Putra Pesantren in Martapura, South Kalimantan. Data analysis used Fisher Exact test.Result: The result of the research showed that male students who smoked as many as 7 people (10.0%), male parent smoked as many as 28 people (40.0%), the teacher smoked 65 people (92.9%), roommates who smoked as many as 34 people (48.6%), the presence of teachers who smoked as many as 47 people (67.1%). The bivariate analysis in this study showed no correlation between smoking behavior of male parents and students smoking behavior (p-value = 0.694), no correlation between teacher smoking status and students smoking behavior (p-value = 1.000), no relationship status smoking a roommate with students smoking behavior (p-value = 1.000), and no relationship of smoking status outside friend's room with students smoking behavior ((p-value = 0.413).Conclusion: There is no correlation between smoking behavior of male parents and santri smoking behavior, there is no correlation between smoking status of the teacher and santri smoking behavior, no relationship of smoking status of roommate with santri smoking behavior, and no relationship of smoking status of outside friends with smoking behavior santri.Â Keywords : Reinforcing factor, Smoking Behaviour, Student